Colorimetric biomimetic sensor systems based on molecularly imprinted polymer membranes for highly-selective detection of phenol in environmental samples - Sergeyeva, T.A.; Chelyadina, D.S.; Gorbach, L.A.; Brovko, O.O.; Piletska, E.V.; Piletsky, S.A.; Sergeeva, L.M.; El’skaya, A.V. (Вiopolymers and Cell, 2014)
Aim. Development of an easy-to-use colorimetric sensor system for fast and accurate detection of phenol in envi- ronmental samples. Methods. Technique of molecular imprinting, method of in situ polymerization of molecularly imprinted polymer membranes. Results. The proposed sensor is based on free-standing molecularly imprinted polymer (MIP) membranes, synthesized by in situ polymerization, and having in their structure artificial binding sites capable of selective phenol recognition. The quantitative detection of phenol, selectively adsorbed by the MIP membranes, is based on its reaction with 4-aminoantipyrine, which gives a pink-colored product. The intensity of staining of the MIP membrane is proportional to phenol concentration in the analyzed sample. Phenol can be detected within the range 50 nM–10 mM with limit of detection 50 nM, which corresponds to the concentrations that have to be detected in natural and waste waters in accordance with environmental protection standards. Stability of the MIP-membrane-based sensors was assessed during 12 months storage at room temperature. Conclusions. The sensor system provides highly-selective and sensitive detection of phenol in both mo- del and real (drinking, natural, and waste) water samples. As compared to traditional methods of phenol detection, the proposed system is characterized by simplicity of operation and can be used in non-laboratory conditions.